Comprehensive immunoprofile analysis of prognostic markers in pancreaticobiliary tract cancers. (17th January 2023) - Kim, Ji Eun; Kim, Hyemin; Kim, Binnari; Chung, Hye Gyo; Chung, Hwe Hoon; Kim, Kyoung Mee; Kim, Seong Hyun; Jeong, Woo Kyoung; Kim, Young Kon; Min, Ji Hye; Heo, Jin Seok; Han, In Woong; et al.
Abstract: Pancreaticobiliary tract cancer has a poor prognosis with unmet needs in a new target treatment. Some studies have reported that an enhancement of T‐cell immunity is associated with a good prognosis. The aim of this study is to investigate the immunoprofile as a prognostic marker of pancreaticobiliary tract cancers. Unresectable pancreatic ductal adenocarcinoma (PDAC, n  = 80) and biliary tract cancer (BTC, n  = 74) diagnosed between January 2012 and December 2018 in Samsung Medical Center were analyzed. Expression levels of CD8, FOXP3, PD‐1, PD‐L1, and CXCL13 in PDAC and BTC tissue samples were examined with immunohistochemical staining, which was evaluated with various clinical factors. In PDAC, higher degree of PD‐L1 expression was significantly associated with shorter overall survival (OS) ( p  = 0.0095). On the other hand, higher infiltrations of PD‐1 + immune cells ( p  = 0.0002) and CD8 + T cells ( p  = 0.0067) were associated with longer OS. In BTC, higher FOXP3 + ( p  = 0.0343) and CD8 + ( p  = 0.0028) cell infiltrations were associated with better survival. Low infiltration of CD8 + ( p  = 0.0148), FOXP3 + ( p  = 0.0208), PD‐1 + ( p  = 0.0318) cells in PDAC, and FOXP3 + cells ( p  = 0.005) in BTC were considerably related to metastasis. In a combined evaluation of clinical factors and immunoprofiles, univariate analysis revealed that operation after chemotherapy ( p  < 0.0001), mass size ( p  = 0.0004), metastasis ( p  = 0.006), PD‐L1 ( p  < 0.0001), PD‐1 ( p  = 0.003) and CD8 ( p  = 0.0063) was significantly associated with OS in PDAC, and CD8 ( p  = 0.007) was statistically related to OS in BTC. In multivariate analysis, prognostic factors were operation after chemotherapy ( p  = 0.021) in PDAC and CD8 ( p  = 0.037) in BTC. Therefore, immunoprofile analysis of cells expressing CD8, FOXP3, PD‐1, and PD‐L1 might have prognostic values in patients with pancreaticobiliary tract cancers. Abstract : Prognostic immunoprofile analysis of CD8, FOXP3, PD‐1, and PD‐L1 in pancreaticobiliary tract cancer.